APPLICATION OF LASER SCAN TECHNOLOGY TO LANDSLIDE MONITORING, VOLUMETRIC CALCULUS AND DEM - Herban, Ioan Sorin; Grecea, Carmen; Babuca, Nicolae Ioan; Bala, Alina Corina (International Multidisciplinary Scientific GeoConference SGEM, 2013)
A high-resolution and accurate recording of the objects in 3D space is of high importance for many subjects of different domains of interest such as monitoring landslides, archaeology, cultural heritage etc. Traditional techniques for 3D data acquisition either restrict the size of the scanned objects or impose demands on the stability and structure of the surface. Topographic surveys or the digital documentation of stratigraphic excavations using total stations, GPS devices or photogrammetrical methods can be a laborious task. Terrestrial 3D imaging laser scanning forms a method to acquire a large number of precise data points in 3D space representing the surface of the objects under investigation. These scanners are an effective tool for the collection of data to create a digital elevation model of the topography of a site as well as of the surface of a single archaeological deposit. Laser scanning is a method that is applicable to document historic buildings or standing archaeological features as walls, columns, monumental statues as well as caves, abris, megaliths or carved rock formations. The acquired data can be used for documentation purposes only, but the further processing provides the possibility for virtual reality modeling for public presentation, restoration planning or virtual reconstruction. Laser scanning technology and the final deliverable, materialized as the three dimensional model of the terrain, emphasizes the importance and the applicability of geodesy in giving proactive solutions to engineering problems. [PUBLICATION ABSTRACT]